PENGKAJIAN PEMANFAATAN DATA TERRA-MODIS UNTUK EKSTRAKSI DATA SUHU PERMUKAAN LAHAN (SPL) BERDASARKAN BEBERAPA ALGORITMA - Prasasti , Indah; Sambodo, Katmoko Ari; Carolita , Ita (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2007)
Land surface temperature (LST) is one primary parameters energy balance on the surface and also as primary climatology variable that controlling long-wave energy flux through atmosphere. The LST data is needed for drought estimating models which based on calculating of soil moisture lavel and/or evapotranspiration. TERRA satellite that brings sensor MODIS (Moderate Resolution Imaging Spectroradiometer) is an evironmental. Observation satellite that can be used for extracting LST data regionally. The MODIS relatively has width coverage; 2330 Km, and spatial resolution 250 m (1 and 2 channel) with high spectral resolution (36 channels), and temporal resolution that almost similar to the previous generation satellite called NOAA.